Formative assessment as a strategy in active methodology in the medical course: an integrative review (Research, Society and Development, 2022)
Active methodologies employ strategies that provide student autonomy, placing them as the main author of the search for teaching. The teaching method uses formative assessment as a tool to develop the student's teaching process so that from the feedback students are able to point out their difficulties in studying. The objective was to highlight the need for an understanding of active teaching methodologies with the use of formative assessment, making visible its pros and cons and its application in today's context within the faculty of medicine. This study is an integrative review with a qualitative approach, aiming to characterize the phenomenon observed in a descriptive and exploratory way. A search was carried out on the CAPES Periodicals Portal between August and September 2022. 83 records were retrieved and, after applying the eligibility criteria, 6 articles were included for the integrative review. The selected works aimed to evaluate the effectiveness of the active methodology in medical courses. In addition, they demonstrate the use of formative assessment as a methodological instrument capable of teaching and learning students. It becomes evident, therefore, that the formative assessment presents itself as a good alternative for the personal and academic evolution of the student, since the active methodology stimulates the growth and autonomy of the student, strengthening the teaching-learning process and the relationship teacher-student with the construction of knowledge and socialization through horizontal teaching and feedback.